99 / 5000 Hasil terjemahan JWT Implementation in Attendance Applications with Fingerprint Validation, Geotagging and Device Checker - Arief Umarjati; Arief Wibowo (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
During the Covid-19 pandemic the government implement the imposition of Large-Scale Social Restrictions (PSBB). This PSBB also has an impact on companies in Jabodetabek including PT Akses Digital Indonesia. In order to comply with regulations given by the government, PT Akses Digital Indonesia has implemented a Work From Home (WFH) policy for its employees. During the implementation of the WFH policy, had difficulty monitoring the performance of its employees. Attendance is one measure of the level of performance, especially employee discipline. Based on the identification of the problem, an employee presence web service application is needed. Of course, this application should be as effective as conventional fingerprint machines in offices. This application is accompanied by a validation feature using geotagging, fingerprint and device checkers to minimize fraud when employees make attendance. This study implements the RESTful API security feature on web services using JSON Web Token (JWT) based on the HMAC SHA-256 algorithm. All implementation stages are tested using the Black Box method and show that JWT can secure the authentication process and secure data. The validation feature is able to provide attendance data with an accuracy of 90,9%.